An Enzymatic Ethanol Biosensor and Ethanol/Air Biofuel Cell Using Liquid-Crystalline Cubic Phases as Hosting Matrices to Co-Entrap Enzymes and Mediators. Issue 7 (1st January 2017) - Wu, Guozhi; Yao, Zhen; Fei, Bailu; Gao, Feng
Abstract : In this study, liquid-crystalline lipidic cubic phases (LCPs) formed by monoolein (MO) were used as hosting matrices to co-entrap enzymes and mediators to fabricate enzyme electrodes for biosensors and enzymatic biofuel cells (BFCs). An ethanol dehydrogenase (ADH)-based bioelectrode was fabricated by co-immobilizing ADH and electrocatalyst, toluidine blue (TB) into MO to form doped LCPs on glassy carbon substrate electrode. The prepared bioelectrode was used for ethanol sensing and bioanode of ethanol/air BFC. The constructed ethanol biosensor displays good linear concentration range from 0 to 15.6 mM with a detection limit of 0.09 mM and was applied for ethanol detection in human serum with satisfactory results. To construct an ethanol/air BFC, a biocathode for oxygen reduction was fabricated by co-immobilizing laccase and redox mediator, 2, 2 ′ -azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS) into MO to form doped LCPs on glassy carbon substrate electrode. The performances of the constructed ethanol/air BFC were characterized in buffer solution and red wine, respectively. The open circuit voltage (OCV) and maximum power density of the ethanol/air BFC are 0.53 V and 12.0 μWcm −2 at 0.36 V in buffer solution, and 0.42 V and 2.78 μW cm −2 at 0.26 V in red wine, respectively.